Pursuing higher acceptability and compliance for electric two-wheeler standardization policy in China: The importance of socio-demographic characteristics, psychological factors, and travel habits. (January 2023) - Li, Xintong; Han, Chunyang; Huang, Helai; Pervez, Amjad; Xu, Guangming; Hu, Cheng; Jiang, Qianshan; Wei, Yulu
Abstract: To improve non-motorized traffic safety, electric two-wheelers (ETWs) standardization policies have been recently introduced in some major Chinese cities. However, their mandatory nature raises concerns about their public acceptability and intention of compliance. This study aims to investigate the factors influencing users' acceptability and intended behavioral reaction to the two major types of ETW standardization policy schemes in the Mainland, China. Based on the Value-Belief-Norm Theory combined with policy-specific perceptions, a Structural Equation Model (SEM) was proposed to analyze the determinants of users' acceptability under each policy scheme. Furthermore, a Multinomial Logit (MNL) model was applied in each scheme to identify key factors affecting users' decisions on their compliance behaviors. To achieve these objectives, a sample of 830 responses was collected from China using a questionnaire survey. The results of the SEM showed an identical psychological mechanism of acceptability in the two schemes. In the mechanism, factors regarding policy-specific perceptions were strong direct determinants of policy acceptability, and perceived policy effectiveness was affected by general environmental beliefs. The MNL model's estimation revealed similar findings for the two schemes: higher levels of acceptability and household income increase users' propensity to engage in compliance behaviors, whereas higher levels of education and frequent use of ETWs reduce it. However, there exists one significant difference between the two schemes as well. The positive effect of the acceptability on intended compliance behaviors in the high and low-income groups would only be equal in a scheme that provides a subsidy. The findings can help improve public acceptability and social compliance, resulting in greater policy effectiveness.